Energizing marginal soils – The establishment of the energy crop Sida hermaphrodita as dependent on digestate fertilization, NPK, and legume intercropping. (April 2016) - Nabel, Moritz; Temperton, Vicky M.; Poorter, Hendrik; Lücke, Andreas; Jablonowski, Nicolai D.
Abstract: Growing energy crops in marginal, nutrient-deficient soils is a more sustainable alternative to conventional cultivation. The use of energy-intensive synthetic fertilizers needs to be reduced, preferably via closed nutrient loops in the biomass production cycle. In the present study based on the first growing season of a mesocosm experiment using large bins outdoors, we evaluated the potential of the energy plant Sida hermaphrodita to grow in a marginal sandy soil. We applied different fertilization treatments using either digestate from biogas production or a commercial mineral NPK-fertilizer. To further increase independence from synthetically produced N-fertilizers, the legume plant Medicago sativa was intercropped to introduce atmospherically fixed nitrogen and potentially facilitate the production of additional S . hermaphrodita biomass. We found digestate to be the best performing fertilizer because it produced similar yields as the NPK fertilization but minimized nitrate leaching. Legume intercropping increased the total biomass yield by more than 100% compared to S . hermaphrodita single cropping in the fertilized variants. However, it negatively influenced the performance of S . hermaphrodita in the following year. We conclude that a successful establishment of S . hermaphrodita for biomass production in marginal soils is possible and digestate application formed the best fertilization method when considering a range of aspects including overall yield, nitrate leaching, nitrogen fixation of M . sativa, and sustainability over time. Highlights: Marginal soil is suitable for biomass production of Sida . hermaphrodita . Digestate or NPK-fertilization strongly increased yield in equal measure. Intercropping with M . sativa increases total biomass yield and fixes additional N. Digestate fertilization positively affected N-fixation and reduced N-leaching.